PEMBUATAN TEMPAT PENSIL BERBAHAN STIK ES KRIM UNTUK EDUKASI SADAR LINGKUNGAN - Aprilia Anggi Fernanda Eka Saputri; Nandika A Koni; Dwilita Latifa Tonggi; Wilan Nusi; Reska Rahmawati Putri Yusuf; Abdul Rahmat; Isnanto Isnanto (Jurnal Sosial Humaniora dan Pendidikan, 2022)
A person's for creative expression in the form of work is called creativity. In order to ensure a brighter future, everyone must be able to work and produce work that is beneficial to both themselves and those around them. John W. Santrock defines character education as instruction that is delivered directly to students in order to instill moral values, educate students about moral knowledge, and make efforts to prevent inappropriate behavior. The easiest way for parents to teach their children to care about the environment is to teach them how to manage waste. Parents need to teach their children how to dispose of trash according to its type as well as where to put it. Start teaching children about the various types of waste and how to either manage or dispose of them. The simplest method is to include children in waste management. When you are sorting waste with your children, don't forget to talk about a few things, like the different kinds of waste, why it's important to separate waste so it doesn't pollute the environment, and the different effects on the environment that can happen if waste isn't handled properly.